Accommodating Stakeholders’ Voices in the Curriculum Development in an Indonesian Higher Education Institution - Siti Nur Hidayah; Wisjnu Martani; Wahyu Supartono (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This article aims to investigate the accommodation of stakeholders’ voices and it’s challenges in the practices of curriculum development. Using a qualitative approach, the primary data was gathered through in-depth interviews with the head and secretary, and the administrative staff of four Study Programs in The School of Post Graduate Program of one of the leading universities in Yogyakarta, Indonesia. Whereas, secondary data was taken from the documents of curriculum reviews and accreditation documents. The research found that amidst the complexity of involving stake holder’s views within curriculum design, all the four programs have gathered the stake holders’ voices via tracer study, informal discussion during academic meetings and evaluation from the students. The accommodation of stake holders’ voices can be traced in the form of the addition of elective courses, merging of some courses, addition or omission of certain courses in the current curriculum design. However, the practice of curriculum development was challenged by various aspects such as the commitment of Study Programs to maintain their ‘scientific core’ vis a vis addressing market demand given their commitment to improve theories and knowledge, and the limitation of human resource availabilityArtikel ini Betjeman untuk meneliti akomodasi terhadap masukan stakeholder serta tantangannya dalam praktik pengembangan kurikulum. Menggunakan pendekatan kualitatif, data primer dikumpulkan melalui wawancara dengan ketua dan sekretaris, dan staf administrasi pada empat program studi di Program Pascasarjana di salah satu universitas terkemuka di Yogyakarta, Indonesia. Sementara itu, data sekunder diambil dari dokumen review kurikulum dan akreditasi. Penelitian ini menemukan bahwa di tengah kompleksitas pelibatan stake holder dalam desain kurikulum, keempat Program Studi mengumpulkan masukan stakeholder melalui tracer study, diskusi informal dalam pertemuan-pertemuan akademik dan evaluasi dari mahasiswa. Akomodasi yang dilakukan Program Study dapat dilacak dalam bentuk penambahan mata kuliah tambahan, penggabungan beberapa mata kuliah, penambahan atau pengurangan mata kuliah tertentu dalam desain kurikulum yang baru. Akan tetapi, pelaksanaan pengembangan kurikulum tersebut menghadapi tantangan berupa komitmen Program Studi untuk mempertahankan ‘inti keilmuan’ dihadapkan dengan bagaimana mengakomodir tuntutan pasar mengingat bahwa Program Studi memiliki komitmen untuk pengembangan teori dan pengetahuan, dan keterbatasan sumber daya manusia di Program Studi.